2023
DOI: 10.1371/journal.pone.0281978
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling Neanderthals’ dispersal routes from Caucasus towards east

Abstract: The study of the cultural materials associated with the Neanderthal physical remains from the sites in the Caucasus, Central Asia and Siberian Altai and adjacent areas documents two distinct techno-complexes of Micoquian and Mousterian. These findings potentially outline two dispersal routes for the Neanderthals out of Europe. Using data on topography and Palaeoclimate, we generated computer-based least-cost-path modelling for the Neanderthal dispersal routes from Caucasus towards the east. In this regard, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Archaeologists working in the Persian Plateau have begun to pay considerable attention to hominin dispersals in the Late Pleistocene 60 , 68 , 69 . A recent climatic and palaeohydrological study has indicated that the region experienced ameliorated conditions in MIS 5 (130–71 kya) and MIS 3 (57–29 kya), consistent with the widespread location of Middle Palaeolithic (MP) sites in the Zagros Mountains and in lowland riverine and lake settings.…”
Section: Resultsmentioning
confidence: 99%
“…Archaeologists working in the Persian Plateau have begun to pay considerable attention to hominin dispersals in the Late Pleistocene 60 , 68 , 69 . A recent climatic and palaeohydrological study has indicated that the region experienced ameliorated conditions in MIS 5 (130–71 kya) and MIS 3 (57–29 kya), consistent with the widespread location of Middle Palaeolithic (MP) sites in the Zagros Mountains and in lowland riverine and lake settings.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, recent research identified also two possible routes for the Neanderthal dispersal from the Caucasus towards the east: a northern route from the Greater Caucasus via the northern Caspian corridor, associated with the Eastern Micoquian distribution to the Altai, and a southern route from the Lesser Caucasus via the southern Caspian corridor, associated with the spread of other Mousterian industries to Central Asia and Altai [ 45 ]. The researchers hypothesize that the two Neanderthal populations and cultural facies that could be associated with the southern route are the makers of the Zagros Mousterian and Levantine Mousterian.…”
Section: Discussionmentioning
confidence: 99%